Publications Received (Academy of Management Review, 1998)
The list consists of publications including: “After Lean Production: Evolving Employment Practices in the World Auto Industry,” edited by Thomas a. Kochan, Russel D. Lansbury, and John Paul MacDuffie; “Cultural Complexity in Organizations: Inherent Contrasts and Contradictions,” by Sonja A. Sackmann; and “Teams at the Top: Unleashing the Potential of Both Teams and Individual Leaders,” by Jon R. Katzenbach.